T THE EFFECT OF WORK ENVIRONMENT AND DISCIPLINE WORK ON EMPLOYEE PERFORMANCE AT CIREBON DISTRICT TRANSPORTATION OFFICE IN NEW NORMAL SITUATION - Sandi Nasrudin Wibowo Wibowo; Eva Triana Hutami (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to know that the effect of work environment and discipline work on employee performance. The research location at Cirebon District Transportation Office. The population of this research is 60 employees. Saturated sample sampling is used to choose all the employees. This research type is quantitative with survey methods. Data collection used questionnaires. Data analysis techniques used multiple linear regression. The result showed that (1) Work environment had a positive and significant effect on employee performance, (2) Discipline work had a positive and significant effect on employee performance, and (3) Work environment and discipline work have a joint effect on employee performance.